Event organizers’ perception of green convention image: the relationship between green image and behavavioural intentions / Muhammad Aliff Asyraff Kamal Nur Zaman - Kamal Nur Zaman, Muhammad Aliff Asyraff (2013)
As public awareness on environmental issues is gradually increasing nowadays, green elements seem as a crucial modern marketing tool that can induce people’s perception and behavioural intentions. Throughout tourism industry, most organizations belief destination image can be enhanced by implementing green practices and obtaining green recognition. To be precise, organizations of convention centre have started to promote themselves as a green convention in order to be sustained in convention industry as well as important for image positioning among the stakeholders. From the above notion, this study attempted to investigate how the perception of green convention centre image (cognitive and overall image) can affect future behavioural intentions (word of mouth and revisit intention). A self-administrated questionnaire was distributed to the selected 49 event organizers by conducting a face to face interview. A series of analyses using descriptive and inferential were used to analyze the data. The results indicate cognitive green convention image has a positive impact on the event organizers’ behavioural intentions. The overall green convention image also found positively related with both favourable behavioural intentions constructs. The role of the overall image as a moderator has been proved as this image component mediates the relationship between cognitive image and behavioural intentions. Theoretically, the results of this study contribute to the convention tourism literatures by providing additional insights into cognitive image, overall image as a mediating variable, word of mouth and revisit intention. The findings will also assist management of convention centre in discovering which cognitive attributes and behavioural intentions constructs that least or most influence their customers’ perception. A range of practical and theoretical implications are discussed.